Mother perception of child nutritional status and toddler food intake - Danumaya, Almira (BKM Public Health and Community Medicine, 2021)
Objective: Nutritional problems in children under five are still significant. Malnutrition can have a negative impact on the growth and health of toddlers. One of the reasons for this can be improper food intake. Inappropriate food intake for toddlers can occur because the wrong perception of the mother influences it. This wrong perception leads to improper feeding as well. This study aims to determine the relationship between mothers' perception of the nutritional status of children under five with food intake (energy, protein, fat, and carbohydrates) under five. Methods: A quantitative observational research design was used with a cross-sectional design. The study was conducted on 45 pairs of mothers and children aged 12-59 months who live in Sleman who were taken by purposive sampling method. The instrument used was a toddler silhouette scale questionnaire, SQ-FFQ, and knowledge of maternal nutrition, which were filled out independently by the respondents. The analytical method used is Fisher's Exact test for bivariate test and stratification analysis with Haenszel Mantel. Result: The nutritional status of children under five in this study mostly (84.4%) had good nutritional status. Most mothers under five (88.9%) have an appropriate perception of the nutritional status of their children. Toddlers in this study mostly had excessive energy intake (80%), excess fat intake (86.6%), excessive carbohydrate intake (71.1%), and all toddlers had excessive protein intake. There is no statistically significant relationship between mothers' perceptions of the nutritional status of their toddlers and their toddler's food intake (p>0.05).